2005
DOI: 10.2519/jospt.2005.35.12.786
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Outcome After Ankle Fracture

Abstract: Mark Stewart, MPH (Hons)3Study Design: Prospective inception cohort study of 62 consecutive patients seen in 2 orthopaedic clinics following ankle fracture. Objectives: To investigate 4 putative predictors (age, fracture classification, acute management [surgical or nonsurgical], and ankle dorsiflexion range of motion measured at the time of cast removal) of outcome after ankle fracture and to develop simple predictive models of outcome after ankle fracture. Background: Ankle fracture is a common condition. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 24 publications
3
47
2
3
Order By: Relevance
“…18 Shivarathre et al in 2011 studied the results of operative fixation for unstable ankle fractures in patients aged over 80 years. The most common fracture pattern was Danis-Weber B type.…”
Section: Inferencementioning
confidence: 99%
“…18 Shivarathre et al in 2011 studied the results of operative fixation for unstable ankle fractures in patients aged over 80 years. The most common fracture pattern was Danis-Weber B type.…”
Section: Inferencementioning
confidence: 99%
“…Factors found to be associated with outcomes after ankle fracture include the type of orthopedic management (surgical or conservative), 11,[53][54][55][56][57] fracture severity, 11,54,[58][59][60][61][62][63][64] ankle range of motion, 54,65 Classifying fracture severity according to the number of malleoli fractured appears to provide a more reliable prediction of outcome. Unimalleolar fracture has been consistently shown to be associated with better outcomes than bimalleolar or trimalleolar fracture.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Unimalleolar fracture has been consistently shown to be associated with better outcomes than bimalleolar or trimalleolar fracture. 54,58,60,62 There is also some indication that baseline ankle dorsiflexion range of motion and pain are independent predictors of function, perceived recovery, and dorsiflexion range of motion in the short and medium term. 54,65 However, further research is required to investigate whether modifying these factors, or selectively providing patients with significant problems in dorsiflexion range of motion and pain with a more intensive rehabilitation program, will lead to better outcomes.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…In addition, the cross-sectional correlations between LT Aff and the LEFS in our study are similar to those reported for patients with an ankle fracture after cast removal (95% CIs for r ¼ 0.07-0.21 at 6 weeks and 0.05-0.20 at 6 months). 1 As Table 3 shows, the validity findings suggest a measurement strategy that may minimize clinical time spent measuring DF-ROM. The absence of a cross-sectional relationship between LT Aff and LEFS and GFAS scores, in the presence of a longitudinal relationship between their change scores, suggests that measurement of LT Aff is a valid means of documenting change.…”
Section: Validitymentioning
confidence: 99%
“…19 Among patients with an ankle fracture, two studies have demonstrated the predictive validity of affected-limb LT scores on activity limitation. 1,20 The present study was designed as an initial parameter estimation study of the psychometric properties of the LT in a sample of orthopaedic patients. Our objectives were to examine the reliability and validity of the LT and to determine the impact on these measurement properties of using a single or multiple series of lunges with one or both limbs.…”
mentioning
confidence: 99%